How Strong are Passwords Used to Protect Personal Health Information in Clinical Trials? - El Emam, Khaled; Moreau, Katherine; Jonker, Elizabeth (Université d'Ottawa | University of Ottawa, 2011)
Background: Findings and statements about how securely personal health information is managed in clinical research are mixed. Objective: The objective of our study was to evaluate the security of practices used to transfer and share sensitive files in clinical trials. Methods: Two studies were performed. First, 15 password-protected files that were transmitted by email during regulated Canadian clinical trials were obtained. Commercial password recovery tools were used on these files to try to crack their passwords. Second, interviews with 20 study coordinators were conducted to understand file-sharing practices in clinical trials for files containing personal health information. Results: We were able to crack the passwords for 93% of the files (14/15). Among these, 13 files contained thousands of records with sensitive health information on trial participants. The passwords tended to be relatively weak, using common names of locations, animals, car brands, and obvious numeric sequences. Patient information is commonly shared by email in the context of query resolution. Files containing personal health information are shared by email and, by posting them on shared drives with common passwords, to facilitate collaboration. Conclusion: If files containing sensitive patient information must be transferred by email, mechanisms to encrypt them and to ensure that password strength is high are necessary. More sophisticated collaboration tools are required to allow file sharing without password sharing. We provide recommendations to implement these practices.
Keywords: privacy; security; passwords